Integrated Communication System: Gesture and language acquisition in typically developing children and children with LD and DLD - Lüke, Carina; Ritterfeld, Ute; Grimminger, Angela; Rohlfing, Katharina; Liszkowski, Ulf (Frontiers in Psychology 11)

Sexuelle Vielfalt in der Religionspädagogik - Uppenkamp, Vera (Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen)

Armut und Reichtum - Uppenkamp, Vera (Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen)

Hören – Sprechen – Lesen – Schreiben. Basale Sprachfähigkeiten. - Topalović, Elvira; Uhl, Benjamin

Hören – Sprechen – Lesen – Schreiben. Basale Sprachfähigkeiten. - Topalović, Elvira; Uhl, Benjamin

Digitales Lesen

"Nous sommes embarqués" oder "Wie wir wurden, was wir sind, indem wir hörten, was die Tonträger uns zutrugen" - Kurze Anmerkungen zu Musik, Kultur und Wissenschaft. - Jacke, Christoph (Texturen. Nr. 7 - Wandeln.)

SJS80CJ - Perspektiven und Perspektiven auf Perspektiven auf/in/aus Kulturen. - Jacke, Christoph (Festschrift für Siegfried J. Schmidt zum 80. Geburtstag. Private Festschrift.)

„I Am Just A Broken Heart” – Zum Tod von Dave Kusworth - Jacke, Christoph (Kaput - Magazin für Insolvenz & Pop.)

Differenz - Kammeyer, Katharina (Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen)

Multimodal approach towards understanding the changes in the autonomic nervous system induced by an ultramarathon. - Vieluf, S; Scheer, V; Hasija, Tanuj; Schreier, PJ; Reinsberger, Claus (Res Sports Med)

Golf spielen gegen die Vergesslichkeit: Effekte des Erlernens der Sportart auf das Default Mode Netzwerk des Gehirns - Ströhlein, Julia Kristin; Vieluf, Solveig; van den Bongard, Franziska; Gölz, Christian Johannes; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Im Rahmen der Demenz vom Alzheimer-Typ (DAT) zeigt sich eine gestörte neuronale Netzwerkorganisation, welche sich unter anderem auch im Default Mode Netzwerk (DMN) widerspiegelt. Multimodale Interventionen, wie zum Beispiel Golf, können einen positiven Einfluss auf die funktionelle Integrität der Netzwerke haben. Methodik Im Rahmen einer Pilotstudie wurde der Einfluss des Erlernens der Sportart Golf bei sieben älteren Menschen (> 60 Jahre) mit subjektiven Gedächtnisbeschwerden auf die funktionelle Konnektivität des DMN untersucht. Die Probanden haben 22 Wochen unter Anleitung eines professionellen Golftrainers dreimal wöchentlich je 60 min trainiert. Vor (Messzeitpunkt 0, MZP0) und nach der Intervention (Messzeitpunkt 1, MZP1) wurde eine Elektroenzephalografie (EEG)-Messung unter Ruhebedingungen (resting-state) durchgeführt. Die EEG-Daten wurden mit einem Magnetresonanztomographie-Template koregistriert. Die Konnektivitätsanalyse wurde in 15 Regionen des DMN durchgeführt und im Längsschnitt verglichen. Dabei wurden die Frequenzbänder beta (14–29 Hz) und theta (5–7 Hz) berücksichtigt. Ergebnisse Nach der Intervention wurde eine höhere funktionelle Konnektivität im gesamten DMN bei 5 / 7 Teilnehmenden im beta Frequenzband bzw. bei 6 / 7 Probanden im theta Frequenzband zu MZP1 im Vergleich zu MZP0 gemessen. Im anterioren DMN war bei allen Probanden und Probandinnen die funktionelle Konnektivität im beta Frequenzband zu MZP1 im Vergleich zu MZP 0 höher, während sie im theta-Band bei 6 von 7 Teilnehmenden niedriger war. Im posterioren DMN war bei 6 von 7 (beta), bzw. 5 von 7 (theta) Probanden und Probandinnen die funktionelle Konnektivität zu MZP1 höher als zu MZP0. Spearman-Korrelationsanalysen zeigen zudem einen Zusammenhang zwischen der Teilnahmehäufigkeit und der prozentualen Veränderung der funktionellen Konnektivität im gesamten DMN des beta Frequenzbandes (r = 0,786, p = 0,036) und im anterioren DMN des theta Frequenzbandes (r = –0,821, p = 0,023). Fazit Auf Basis der vorliegenden Daten lässt sich vermuten, dass das Erlernen der Sportart Golf einen Einfluss auf das DMN haben könnte. Die Ergebnisse bilden die Grundlage für die Planung einer Studie mit einer größeren Kohorte und randomisierten kontrollierten Design.

Effects of force level and task difficulty on force control performance in elderly people - Strote, Caren; Gölz, Christian Johannes; Stroehlein, Julia Kristin; Haase, Franziska Katharina; Koester, Dirk; Reinsberger, Claus; Vieluf, Solveig (Experimental Brain Research)
Abstract As the proportion of people over 60 years of age rises continuously in westernized societies, it becomes increasingly important to better understand aging processes and how to maintain independence in old age. Fine motor tasks are essential in daily living and, therefore, necessary to maintain. This paper extends the existing literature on fine motor control by manipulating the difficulty of a force maintenance task to characterize performance optima for elderly. Thirty-seven elderly ( M = 68.00, SD = 4.65) performed a force control task at dynamically varying force levels, i.e. randomly changing every 3 s between 10%, 20%, and 30% of the individual’s maximum voluntary contraction (MVC). This task was performed alone or with one or two additional tasks to increase task difficulty. The force control characteristics accuracy, variability, and complexity were analyzed. Lowest variability was observed at 20%. Accuracy and complexity increased with increasing force level. Overall, increased task difficulty had a negative impact on task performance. Results support the assumption, that attention control has a major impact on force control performance in elderly people. We assume different parameters to have their optimum at different force levels, which remain comparably stable when additional tasks are performed. The study contributes to a better understanding of how force control is affected in real-life situations when it is performed simultaneously to other cognitive and sensory active and passive tasks.
Keywords: General Neuroscience

Self-lubricating coatings via PDMS micro-gel dispersions - Ressel, Joerg; Seewald, Oliver; Bremser, Wolfgang; Reicher, Hans-Peter; Strube, Oliver I. (Progress in Organic Coatings)

Contrast variation of micelles composed of Ca2+ and block copolymers of two negatively charged polyelectrolytes - Carl, Nico; Prévost, Sylvain; Schweins, Ralf; Huber, Klaus (Colloid and Polymer Science)
Abstract Block copolymers were prepared with two anionic polyelectrolyte blocks: sodium polyacrylate (PA) and sodium polystyrene sulfonate (PSS), in order to investigate their phase behavior in aqueous solution in the presence of Ca 2+ cations. Depending on the concentration of polymer and Ca 2+ and on the ratio of the block lengths in the copolymer, spherical micelles were observed. Micelle formation arises from the specific interaction of Ca 2+ with the PA block only. An extensive small-angle scattering study was performed in order to unravel the structure and dimensions of the block copolymer micelles. Deuteration of the PA block enabled us to perform contrast variation experiments using small-angle neutron scattering at variable ratios of light and heavy water which were combined with information from small-angle X-ray scattering and dynamic light scattering.
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

The Molecular Mechanism of Polymer Formation of Farnesylated Human Guanylate-binding Protein 1 - Sistemich, Linda; Kutsch, Miriam; Hämisch, Benjamin; Zhang, Ping; Shydlovskyi, Sergii; Britzen-Laurent, Nathalie; Stürzl, Michael; Huber, Klaus; Herrmann, Christian (Journal of Molecular Biology)
Keywords: Molecular Biology; Structural Biology

Self‐Assembly of Pseudo‐Isocyanine Chloride as a Sensor for Macromolecular Crowding In Vitro and In Vivo - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Self‐Assembly of Pseudo‐Isocyanine Chloride as a Sensor for Macromolecular Crowding In Vitro and In Vivo - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Sport and Physical Activity in Epilepsy. - van den Bogard, F; Hamer, HM; Sassen, R; Reinsberger, Claus (Dtsch Arztebl Int)

Autonomic nervous system changes detected with peripheral sensors in the setting of epileptic seizures. - Vieluf, S; Reinsberger, Claus; El Atrache, R; Jackson, M; Schubach, S; Ufongene, C; Loddenkemper, T; Meisel, C (Sci Rep)

Match Situations Leading to Head Injuries in Professional Male Football (Soccer)-A Video-Based Analysis Over 12 Years. - Beaudouin, F; Aus der Fünten, K; Tröß, T; Reinsberger, Claus; Meyer, T (Clin J Sport Med)

Neurology - Reinsberger, Claus (Injury and health risk management in sports - a guide to decision making)

Kat.-Nr.23. Nigerianische Helmmaske - Duschner, Paul (Geschichte der Dinge. Zur Herkunft der Objekte in nordrhein-westfälischen Sammlungen)

3. Alles unter dem Himmel - Das Museum für Ostasiatische Kunst in Köln. Köln 2019. Hrsg. Museum für Ostasiatische Kunst Köln. Texte von Adele Schlombs, Christel und Dieter Schürzeberg, Helwig Schmidt-Glintzer, u.a. - Duschner, Paul (Ostasiatische Zeitschrift)

27. Regionalgeschichtstagung: Mythos und historische Wahrheit – ein prekäres Verhältnis - Duschner, Paul (Paderborner Historische Mitteilungen)

Ostasiatika in Paderborn: Zur Sammlung Sigrid Tenge-Erb und Richard Erb - Duschner, Paul (Paderborner Historische Mitteilungen)

Development of a special specimen geometry for the experimental determination of fracture mechanical parameters of clinchable metal sheets - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter

Experimental and numerical preliminary investigations of the base material and preformed components regarding fatigue crack growth in joined structures - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter

Postoperative Versorgung des Charcot-Fußes mittels Unterschenkelorthese – aktueller Stand der Versorgung und Perspektiven der additiven Fertigung - Schafran, Tommy; Schraeder, Dirk Theodor; Schramm, Britta; Kullmer, Gunter

Westfalen in der Vormoderne. Studien zur mittelalterlichen und frühneuzeitlichen Landesgeschichte, 32 Bde.

Wirkungsmessung bei sozialen Sportprojekten im Kontext der Entwicklungszusammenarbeit: Methodische Überlegungen und Herausforderungen. - Petry, K.; Bauer, K.; Biermann, Marie (Sport im Kontext von internationaler Zusammenarbeit und Entwicklung: Perspektiven und Herausforderungen im Spannungsfeld von Wissenschaft, Politik und Praxis.)

11kW, 70kHz LLC Converter Design with Adaptive Input Voltage for 98% Efficiency in an MMC - Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (2020 IEEE 21st Workshop on Control and Modeling for Power Electronics (COMPEL))
Although there are numerous design methodologies for the LLC resonant converter, they often do not consider the possibility of input voltage adjustment. In the proposed concept, a modular multi-level converter (MMC) is used to step-down the three-phase medium voltage of 10 kV, and provide up to 1 MW of pure DC power to the load consisting of electrolyzers for hydrogen generation. Therefore, each module is extended by an LLC resonant converter to adapt to the specific electrolyzers DC voltage range of 142...220 V and to provide galvanic isolation. In order to achieve a high efficiency for a wide range of load conditions, the input voltage of the LLC converter is adjusted between 600 V and 770 V while operating at resonance or close to resonance. The parameters of the 11kW LLC resonant converter with an integrated leakage inductance are systematically optimized to maximize the efficiency for all loads while achieving zero-voltage switching. For a fast estimation of eddy current losses, a new method is proposed, which uses a single FEM simulation to fit newly developed loss equations. The calculated average efficiency is 97.8%. The prototype of the LLC converter reaches a peak efficiency of over 98% at resonance at half load which is similar to the precalculated value.

Integrierte Modellierung von Zuverlässigkeit und dynamischem Verhalten mechatronischer Systeme - Kaul, Thorben
Die digitale Transformation prägt die Entwicklung intelligenter technischer Systeme, welche durch Vernetzung und inhärente Intelligenz einen weiten Funktionsumfang aufweisen. Selbstoptimierende Systeme sind als Stellvertreter der Klasse intelligenter Systeme durch die autonome zielkonforme Adaption des Systemverhaltens charakterisiert. Dabei stellen mechatronische Systeme eine der Grundlagen dieser Systemklasse dar, indem die Umwelt- und Betriebsbedingungen sowie die Systemzustände sensorisch erfasst und das dynamische Systemverhalten zielgerichtet beeinflusst werden. Der große Funktionsumfang intelligenter technischer Systeme geht mit einer Zunahme der Systemkomplexität einher, die eine Herausforderung bei der Absicherung der Verlässlichkeit darstellt. Dem gegenüber bieten insbesondere selbstoptimierende Systeme Potenziale zur Steigerung der Verlässlichkeit. Die Umsetzung entsprechender Maßnahmen erfordert die Unterstützung des Entwicklungsprozesses durch geeignete Methoden. Die Beherrschung der zunehmenden Systemkomplexität ist durch die Verwendung vorhandener Modelle des Entwicklungsprozesses möglich, wird aber in aktuellen Methoden nicht umfänglich genutzt. Das Ziel ist die Absicherung der Verlässlichkeit bereits in frühen Entwicklungsphasen bis hin in späte Lebenszyklusphasen. Es wird eine Methode für die integrierte Modellierung der Zuverlässigkeit, als zentrale Kenngröße der Verlässlichkeit, und des dynamischen Systemverhaltens entwickelt. Anhand von drei Anwendungsbeispielen wird gezeigt, dass diese Methode die Entwicklung von Maßnahmen zur Steigerung der Verlässlichkeit in selbstoptimierenden Systemen ermöglicht, auf komplexe Systeme anwendbar ist und die Absicherung der Verlässlichkeit während des Betriebs mit Hilfe eines Digitalen Zwillings unterstützt.
Keywords: Integrierte Modellierung; geschlossene Modellierung; mechatronische Systeme; intelligente Systeme; Zuverlässigkeit; Dynamische Bayes’sche Netze; Verlässlichkeit; Systemzuverlässigkeit; Digitaler Zwilling; selbstoptimierende Systeme; Mehrzieloptimierung

Kurzzeitaustenitisierung höchstfester Stähle – eine zeiteffiziente Methode zur Fertigung sicherheitsrelevanter Bauteile mit verbesserten Eigenschaften - Andreiev, Anatolii

Development of SLM Ni-based Superalloys and Investigation of Corrosion Behavior in Chloride-containing Environments - Wooldridge, Madison

Properties of bright squeezed vacuum at increasing brightness - Sharapova, Polina R.; Frascella, G.; Riabinin, M.; Pérez, A. M.; Tikhonova, O. V.; Lemieux, S.; Boyd, R. W.; Leuchs, G.; Chekhova, M. V. (Physical Review Research)
Keywords: General Engineering

Spatial entanglement and state engineering via four-photon Hong–Ou–Mandel interference - Ferreri, A; Ansari, V; Brecht, Benjamin; Silberhorn, Christine; Sharapova, Polina R. (Quantum Science and Technology)
Abstract The phenomenon of entanglement is the basis of quantum information and quantum communication processes. Entangled systems with a large number of photons are of great interest at present because they provide a platform for streaming technologies based on photonics. In this paper we present a device which operates with four-photons and based on the Hong–Ou–Mandel interference. The presented device allows to maximize the degree of spatial entanglement and generate the highly entangled four-dimensional Bell states. Furthermore, the use of the interferometer in different regimes leads to fast interference fringes in the coincidence probability with period of oscillations twice smaller than the pump wavelength. We have a good agreement between theoretical simulations and experimental results.
Keywords: Electrical and Electronic Engineering; Physics and Astronomy (miscellaneous); Materials Science (miscellaneous); Atomic and Molecular Physics; and Optics

Inklusion im Kinder- und Jugendsport unter besonderer Berücksichtigung der Heterogenitätsdimension Behinderung. - Radtke, Sabine; Adolph-Börs, Cindy (Vierter Deutscher Kinder- und Jugendsportbericht. Gesundheit, Leistung und Gesellschaft.)

Lernaufgaben im inklusiven Sprachunterricht. - Topalović, Elvira; Uhl, Benjamin (Inklusion und Kooperation. Fördermagazin Grundschule)

Digitales Lesen: Empirische Evidenzen für den Deutschunterricht - Topalović, Elvira (Der Deutschunterricht)

Sprachliches und literarisches Lernen mit Texten in einfacher Sprache. Deutschdidaktische Kontroversen am Beispiel des Romans „Tschick“. - Topalović, Elvira; Diederichs, Lara (Sprache als Herausforderung – Literatur als Ziel. Kinder- und jugendliterarische Texte und Medien als Ressource für sprachsensibles Lernen.)

Wortgruppen entdecken. - Lang, Susanne; Topalović, Elvira (Praxis Deutsch)

Die Wortgruppe als Rechtschreib- und Lesestrategie. - Topalović, Elvira; Lang, Susanne (In: Lernen lernen. Fördermagazin Grundschule)

Crux of Using the Cascaded Emission of a Three-Level Quantum Ladder System to Generate Indistinguishable Photons - Schöll, E; Schweickert, L; Hanschke, L; Zeuner, K.D; Sbresny, F; Lettner, T; Trivedi, R; Reindl, M; Covre da Silva, S.F; Trotta, R; Finley, J.J; Vučković, J; et al.

Atomistic defects as single-photon emitters in atomically thin MoS2 - Barthelmi, K; Klein, J; Hötger, A; Sigl, L; Sigger, F; Mitterreiter, E; Rey, S; Gyger, S; Lorke, M; Florian, M; Jahnke, F; Taniguchi, T; et al.

Origin of Antibunching in Resonance Fluorescence - Hanschke, L; Schweickert, L; Camilo López Carreño, J; Schöll, E; Zeuner, K.D; Lettner, T; Zubizarreta Casalengua, E; Reindl, M; Covre da Silva, S.F; Trotta, R; Finley, J.J; Rastelli, A; et al.

NbTiN thin films for superconducting photon detectors on photonic and two-dimensional materials - Steinhauer, S; Yang, , L; Gyger, S; Lettner, T; Errando-Herranz, C; Jöns, Klaus D; Baghban, M.A; Gallo, K; Zichi, J; Zwiller, V

A GaAs quantum dot in a parabolic microcavity tuned to 87Rb D1 - Lettner, T; Zeuner, K.D; Schöll, E; Huang, H; Scharmer, S; Covre da Silva, S.F; Gyger, S; Schweickert, L.K; Rastelli, A; Jöns, Klaus D.; Zwiller, V

Entwicklung eines Konzepts zum qualitätsorientierten Monitoring von Social Media in der zivilen Gefahrenabwehr - Habdank, Matthias

On noise-to-state stability of stochastic discrete-time systems via finite-step Lyapunov functions - Noroozi, Navid; Jackson, Roxanne; Quevedo, Daniel E.; Wirth, Fabian R.; Findeisen, Rolf (2019 IEEE 58th Conference on Decision and Control (CDC))

Defensive deception against reactive jamming attacks in remote state estimation - Ding, K.; Ren, X.; Quevedo, D. E.; Dey, S.; Shi, L. (Automatica)

Der Mehrwert Komparativer Theologie für eine die Pluralität ernst nehmende Religionspädagogik - Kamcili-Yildiz, Naciye; Tautz, Monika (Dialog und Transformation. Auf dem Weg zu einer pluralistischen Religionspädagogik)

„Andere Religionen“ in den Curricula der islamischen Religionslehrerausbildung - Kamcili-Yildiz, Naciye (Theo-Web. Zeitschrift für Religionspädagogik)

Mindsets guter Lehre in Beziehung zu den Mindsets religiöser Pluralität - Kamcili-Yildiz, Naciye; Reis, Oliver; Mauritz, Gerrit; Hillebrand, Miriam; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik)

Mechatronischer Entwurf eines geregelten Federungssystems für mittelschwere gepanzerte Kettenfahrzeuge - Gense, Alexander

Produkttolerante Automation zellenbasierter Fertigungssysteme - Bertelsmeier, Fabian

Qur’anic Intertextuality with Jewish-Rabbinic Tradition: the Case of ‘the Cow’ in Q 2:67-74 - Aghaei Abrandabadi, Seyed Ali (Reading the Bible in the Context of Islam)

The Common Link and its Relation to the Hadith Terminology - Aghaei Abrandabadi, Seyed Ali (Modern Hadith Studies: Continuing Debates and New Approaches)

Zuordnungsverfahren für Tauschbörsen - N., N.

Bilder verstehen – Bilder gebrauchen (Modul 4) - Blachut, Alisa (Deutsch lernen: Sprechen – Zuhören – Lesen – Schreiben. DaM – DaZ – DaF. Arbeitsheft 2)

Schutte, Valerie / Paranque, Estelle: Forgotten Queens in Medieval and Early Modern Europe. Political Agency, Myth-Making, and Patronage - Foerster, Anne (Das Mittelalter)

Kane, Bronach C: Popular Memory and Gender in Medieval England. Men, Women and Testimony in the Church Courts, c.1200–1500 - Foerster, Anne (H-Soz-Kult)

Drews, Wolfram: Die Interaktion von Herrschern und Eliten in imperialen Ordnungen des Mittelalters - Foerster, Anne (DA)

Systematische Wahl einer Modellierungstiefe im Entwurfsprozess mechatronischer Systeme - Lochbichler, Matthias

Lebensdauerprognose für additiv gefertigte Kunststoffbauteile mittels bruchmechanischer Konzepte - Bauer, Benjamin

In Zeiten von p-hacking und fake science: Wissenschaftsorientierung als Herausforderung an die Psychologiedidaktik - Scharlau, Ingrid; Schreiber, Christine (Psychologie unterrichten in Deutschland, Österreich und der Schweiz: Leitlinien und Grundlagen)
Keywords: Unterrichtsfach Psychologie

Psychologiedidaktik durch Kommunikationsanalyse - Scharlau, Ingrid; Schreiber, Christine; Patrzek, Justine (Psychologiedidaktik und Evaluation XIII)
Keywords: Unterrichtsfach Psychologie

Towards Quantum One-Time Memories from Stateless Hardware - Broadbent, Anne; Gharibian, Sevag; Zhou, Hong-Sheng (Proceedings of the 15th Conference on the Theory of Quantum Computation, Communication and Cryptography (TQC))
A central tenet of theoretical cryptography is the study of the minimal assumptions required to implement a given cryptographic primitive. One such primitive is the one-time memory (OTM), introduced by Goldwasser, Kalai, and Rothblum [CRYPTO 2008], which is a classical functionality modeled after a non-interactive 1-out-of-2 oblivious transfer, and which is complete for one-time classical and quantum programs. It is known that secure OTMs do not exist in the standard model in both the classical and quantum settings. Here, we propose a scheme for using quantum information, together with the assumption of stateless (i.e., reusable) hardware tokens, to build statistically secure OTMs. Via the semidefinite programming-based quantum games framework of Gutoski and Watrous [STOC 2007], we prove security for a malicious receiver, against a linear number of adaptive queries to the token, in the quantum universal composability framework. We prove stand-alone security against a malicious sender, but leave open the question of composable security against a malicious sender, as well as security against a malicious receiver making a polynomial number of adaptive queries. Compared to alternative schemes derived from the literature on quantum money, our scheme is technologically simple since it is of the "prepare-and measure" type. We also show our scheme is "tight" according to two scenarios.

On efficiently solvable cases of Quantum k-SAT - Gharibian, Sevag; Aldi, Marco; de Beaudrap, Niel; Saeedi, Seyran (Communications in Mathematical Physics)

Communication and Capitalism. A Critical Theory - Fuchs, Christian

Marxism. Karl Marx’s Fifteen Key Concepts for Cultural and Communication Studies. Key Ideas in Media & Cultural Studies Series - Fuchs, Christian

Nationalism on the Internet: Critical Theory and Ideology in the Age of Social Media and Fake News - Fuchs, Christian

Towards a Critical Theory of Communication as Renewal and Update of Marxist Humanism in the Age of Digital Capitalism - Fuchs, Christian (Journal for the Theory of Social Behaviour)

Communicative Socialism/Digital Socialism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Marx heute. Eine Einführung in die kritische Theorie der Kommunikation, der Kultur, der digitalen Medien und des Internets - Fuchs, Christian

Kommunikation und Kapitalismus. Eine kritische Theorie - Fuchs, Christian

Alltagsleben und Alltagskommunikation im Coronavirus-Kapitalismus - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Everyday Life and Everyday Communication in Coronavirus Capitalism - Fuchs, Christian (tripleC: Communication)

The Utopian Internet, Computing, Communication, and Concrete Utopias - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Erich Fromm and the Critical Theory of Communication - Fuchs, Christian (Humanity & Society)

The Ethics of the Digital Commons - Fuchs, Christian (Journal of Media Ethics)

Sosyal Medya: Eleştirel Bir Giriş - Fuchs, Christian

Beitrag zur Steigerung der Qualität von Aluminium-Lichtbogen-Bolzenschweißverbindungen mit Hubzündung - Hader, Christoph

Ersatzmodellentwicklung zur Prognose des kerbinduzierten Fügeteilversagens von Halbhohlstanznietverbindungen unter Crashbelastung - Porsch, Tony

Entwicklung des Prägeelementschweißens für Aluminium-Stahl-Verbindungen im Karosseriebau - Pietsch, Tommy

Qualifizierung intelligenter Datenanalysemethoden bei vollautomatisierten Klebtechnikanwendungen - Sierak, Paulina

Entwicklung einer Methodik zur numerischen Simulation des Hochgeschwindigkeits-Bolzensetzens - Gerkens, Michael

Imaginary quadratic number fields with class groups of small exponent - Elsenhans, Andreas-Stephan; Klüners, Jürgen; Nicolae, Florin (Acta Arithmetica)
Let D<0 be a fundamental discriminant and denote by E(D) the exponent of the ideal class group Cl(D) of K=ℚ(√D). Under the assumption that no Siegel zeros exist we compute all such D with E(D) dividing 8. We compute all D with |D| ≤ 3.1⋅10²⁰ such that E(D) ≤ 8.
Keywords: Algebra and Number Theory

The conductor density of local function fields with abelian Galois group - Klüners, Jürgen; Müller, Raphael (Journal of Number Theory)
We give an exact formula for the number of G-extensions of local function fields Fq((t)) for finite abelian groups G up to a conductor bound. As an application we give a lower bound for the corresponding counting problem by discriminant.
Keywords: Algebra and Number Theory

Modellierung des Strömungs- und Trennverhaltens viskoser Gemische in Packungskolonnen basierend auf tomographischen Untersuchungen - Große Daldrup, Anna

数字时代的资本主义、父权制、奴隶制与种族主义 - Fuchs, Christian (国外社会科学前沿 (Studies on Foreign Social Sciences))

Interview mit Christian Fuchs: »Der Sozialismus ist keine App und kann nicht aus dem Internet heruntergeladen werden«. Marx’ Vision der befreiten Gesellschaft bleibt im digitalen Zeitalter aktuell - Fuchs, Christian (Das Argument)

Vida e comunicação cotidianas no capitalism da coronavirus - Fuchs, Christian (MATRIZes)

Chemical and Morphological Transition of Poly(acrylonitrile)/Poly(vinylidene Fluoride) Blend Nanofibers during Oxidative Stabilization and Incipient Carbonization - Wortmann, Martin; Frese, Natalie; Mamun, Al; Trabelsi, Marah; Keil, Waldemar; Büker, Björn; Javed, Ali; Tiemann, Michael; Moritzer, Elmar; Ehrmann, Andrea; Hütten, Andreas; Schmidt, Claudia; et al. (Nanomaterials)
Thermally stabilized and subsequently carbonized nanofibers are a promising material for many technical applications in fields such as tissue engineering or energy storage. They can be obtained from a variety of different polymer precursors via electrospinning. While some methods have been tested for post-carbonization doping of nanofibers with the desired ingredients, very little is known about carbonization of blend nanofibers from two or more polymeric precursors. In this paper, we report on the preparation, thermal treatment and resulting properties of poly(acrylonitrile) (PAN)/poly(vinylidene fluoride) (PVDF) blend nanofibers produced by wire-based electrospinning of binary polymer solutions. Using a wide variety of spectroscopic, microscopic and thermal characterization methods, the chemical and morphological transition during oxidative stabilization (280 °C) and incipient carbonization (500 °C) was thoroughly investigated. Both PAN and PVDF precursor polymers were detected and analyzed qualitatively and quantitatively during all stages of thermal treatment. Compared to pure PAN nanofibers, the blend nanofibers showed increased fiber diameters, strong reduction of undesired morphological changes during oxidative stabilization and increased conductivity after carbonization.

Humidity-Mediated Anisotropic Proton Conductivity through the 1D Channels of Co-MOF-74 - Javed, Ali; Strauss, Ina; Bunzen, Hana; Caro, Jürgen; Tiemann, Michael (Nanomaterials)
Large Co-MOF-74 crystals of a few hundred micrometers were prepared by solvothermal synthesis, and their structure and morphology were characterized by scanning electron microscopy (SEM), IR, and Raman spectroscopy. The hydrothermal stability of the material up to 60 °C at 93% relative humidity was verified by temperature-dependent XRD. Proton conductivity was studied by impedance spectroscopy, using a single crystal. By varying the relative humidity (70–95%), temperature (21–60 °C), and orientation of the crystal relative to the electrical potential, it was found that proton conduction occurs predominantly through the linear, unidirectional (1D) micropore channels of Co-MOF-74, and that water molecules inside the channels are responsible for the proton mobility by a Grotthuss-type mechanism.

The influence of motor tasks and cut-off parameter selection on artifact subspace reconstruction in EEG recordings - Anders, Phillipp; Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Medical & Biological Engineering & Computing)
Advances in EEG filtering algorithms enable analysis of EEG recorded during motor tasks. Although methods such as artifact subspace reconstruction (ASR) can remove transient artifacts automatically, there is virtually no knowledge about how the vigor of bodily movements affects ASRs performance and optimal cut-off parameter selection process. We compared the ratios of removed and reconstructed EEG recorded during a cognitive task, single-leg stance, and fast walking using ASR with 10 cut-off parameters versus visual inspection. Furthermore, we used the repeatability and dipolarity of independent components to assess their quality and an automatic classification tool to assess the number of brain-related independent components. The cut-off parameter equivalent to the ratio of EEG removed in manual cleaning was strictest for the walking task. The quality index of independent components, calculated using RELICA, reached a maximum plateau for cut-off parameters of 10 and higher across all tasks while dipolarity was largely unaffected. The number of independent components within each task remained constant, regardless of the cut-off parameter used. Surprisingly, ASR performed better in motor tasks compared with non-movement tasks. The quality index seemed to be more sensitive to changes induced by ASR compared to dipolarity. There was no benefit of using cut-off parameters less than 10.
Keywords: Computer Science Applications; Biomedical Engineering

Modulations of Inter-Hemispherical Phase Coupling in Human Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Neuroscience)
Keywords: General Neuroscience

Ethik-Briefing. Leitfaden für eine verantwortungsvolle Entwicklung und Anwendung von KI-Systemen - Matzner, Tobias; Heesen, Jessica; Grundwald, Armin; Roßnagel, Alexander (der Plattform Lernende Systeme)

Digital ist anders — Über eine Universität ohne Präsenzlehre - Matzner, Tobias (Medium.com)

Mediensucht? Über die Medikalisierung der Mediennutzung in Suchtdebatten - Matzner, Tobias (Die dunklen Seiten des Konsums – Alte Probleme, neue Herausforderungen)